Antibody facilitation of multiple sclerosis-like lesions in a nonhuman primate. - Genain, C P (1995)
In the human disease multiple sclerosis (MS), the immune mechanisms responsible for selective destruction of central nervous system myelin are unknown. In the common marmoset Callithrix jacchus, a unique demyelinating form of experimental allergic encephalomyelitis resembling MS can be induced by immunization with whole myelin. Here we show that the MS-like lesion can be reproduced by immunization against the extracellular domain of a single myelin protein, myelin/oligodendrocyte glycoprotein (MOG). By contrast, immunization against the quantitatively major myelin proteins myelin basic protein or proteolipid protein results in inflammation but little or no demyelination. Furthermore, in the presence of encephalitogenic (e.g., disease-inducing) T cells, the fully demyelinated lesion is reconstructed by systemic administration of IgG purified from whole myelin-, or MOG-immunized animals, and equally by a monoclonal antibody against MOG, but not by control IgG. Encephalitogenic T cells may contribute to the MS-like lesion through disruption of the blood-brain barrier that permits access of demyelinating antibody into the nervous system. The identification of MOG as a major target antigen for autoimmune demyelination in a nonhuman primate should facilitate development of specific immunotherapies for human MS.